Transcriptional Activation of the Chlorocatechol Degradative Genes of Ralstonia eutropha NH9 - Ogawa, Naoto (American Society for Microbiology, 1999)
Ralstonia eutropha (formerly Alcaligenes eutrophus) NH9 degrades 3-chlorobenzoate via the modified ortho-cleavage pathway. A ca. 5.7-kb six-gene cluster is responsible for chlorocatechol degradation: the cbnABCD operon encoding the degradative enzymes (including orfX of unknown function) and the divergently transcribed cbnR gene encoding the LysR-type transcriptional regulator of the cbn operon. The cbnRAB orfXCD gene cluster is nearly identical to the chlorocatechol genes (tcbRCD orfXEF) of the 1,2,4-trichlorobenzene-degrading bacterium Pseudomonas sp. strain P51. Transcriptional fusion studies demonstrated that cbnR regulates the expression of cbnABCD positively in the presence of either 3-chlorobenzoate or benzoate, which are catabolized via 3-chlorocatechol and catechol, respectively. In vitro transcription assays confirmed that 2-chloro-cis,cis-muconate (2-CM) and cis,cis-muconate (CCM), intermediate products from 3-chlorocatechol and catechol, respectively, were inducers of this operon. This inducer-recognizing specificity is different from those of the homologous catechol (catBCA) and chlorocatechol (clcABD) operons of Pseudomonas putida, in which only the intermediates of the regulated pathway, CCM for catBCA and 2-CM for clcABD, act as significant inducers. Specific binding of CbnR protein to the cbnA promoter region was demonstrated by gel shift and DNase I footprinting analysis. In the absence of inducer, a region of ca. 60 bp from position −20 to position −80 upstream of the cbnA transcriptional start point was protected from DNase I cleavage by CbnR, with a region of hypersensitivity to DNase I cleavage clustered at position −50. Circular permutation gel shift assays demonstrated that CbnR bent the cbnA promoter region to an angle of 78° and that this angle was relaxed to 54° upon the addition of inducer. While a similar relaxation of bending angles upon the addition of inducer molecules observed with the catBCA and clcABD promoters may indicate a conserved transcriptional activation mechanism of ortho-cleavage pathway genes, CbnR is unique in having a different specificity of inducer recognition and the extended footprint as opposed to the restricted footprint of CatR without CCM.